International Perspectives on ELT Classroom Interaction - Jenks, Christopher J. author. aut Link
XIII, 254 p.
Keywords: This book gathers together 11 empirical-based studies of classroom interaction carried out in different countries, including the USA, England, Kenya, Sweden, and China. Along with a state-of-the-art literature review, the chapters provide key insights and engagement priorities that will prove relevant to a variety of learning and teaching contexts.